The Wonderful Wizard of Oz : Oz #1 - Baum, L. Frank 1856-1919 (Lyman Frank); Denslow, W. W. (William Wallace), 1856-1915. (New York : Books of Wonder, 2000)
After a cyclone transports her to the land of OZ, Dorothy must seek out the great wizard in order to return to Kansas.
Facsimile of the first edition (Chicago : G.M. Hill Co., 1900) with an afterword (p. 262-267) by Peter Glassman.
BL 12/01/00
0812
Keywords: Fantasy; Oz (Imaginary place) -- Juvenile fiction; Wizard of Oz (Fictitious character) -- Juvenile fiction